Struktur Geologi Berdasarkan Citra Pada Anak Gunung Krakatau - Citra Wahyuningrum; Daninta Handalia; Muhammad Rizki Ibrahim (Lembaga Pengembangan Kinerja Dosen, 2023)
Volcano monitoring is crucial, especially for a country with many volcanoes like Indonesia. One of the challenges faced in monitoring active volcanoes is the relatively large cost and the location of the volcano which is difficult to access. Geological structures can be identified and studied using imagery, including satellite imagery and aerial imagery. Although the images do not provide a direct picture of the lithological details of the rock, they can provide important information about the pattern and structural characteristics. Aerial photo acquisition for photogrammetry was carried out using a drone that was flown over the Anak Krakatau Volcano. The results of this photogrammetry can be used as a basis for assessing the Geological Structure of Anak Krakatau Volcano. The use of satellite imagery in monitoring volcanoes provides important information for public safety, scientific research, and understanding of volcanic processes. With advances in technology and the accessibility of satellite imagery data, we can gain a better understanding of volcanic activity, monitor changes, and provide early warning to people living in affected areas.